Digital Transformation in KITE Management (Easy Import for Export Purposes): Viewed from Administrative Process, Technological Aspects, and Human Readiness - Ghina, Aluka; Rustam, Rinaldi; Syofyan, Syofriza (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The Indonesian government is trying to increase export activities through community involvement, especially local entrepreneurs. Digital transformation is the main foundation for optimizing business, especially in the management of Ease of Import for Export Destinations (KITE). This research, using qualitative descriptive methods, explores the impact of digitalization on KITE management through the KITE Application. The research focus includes administrative process changes, technology usability, application effectiveness, data integrity, data security management, training policies, internal evaluations, fine policies, and user perceptions of the transition to the digital era. International trade, especially through ASEAN and AFTA, is an important focus for stimulating economic growth, with DJBC playing a key role in providing fiscal incentives and investment protection. KITE facilities provide important support for entrepreneurs in increasing production and managing company finances. Digital transformation, especially through the Ceisa application, is considered a step forward in customs services. Despite an increase in user satisfaction, further efforts are needed to achieve service stability and optimization. This research, through a qualitative approach and NVivo analysis, provides valuable insights regarding the implementation of the KITE Application and its impact on Indonesian exports, with the hope of providing recommendations for improving implementation, data security, and user response in the era of digital transformation.